2019
DOI: 10.1002/slct.201904112
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen Formation during the Oxygen Reduction Reaction in DMSO LiTFSI on Lithium Air Battery Carbon Electrodes

Abstract: Formation of singlet oxygen,1O2, during the O2 electroreduction reaction (ORR) on carbon electrode in Lithium bis‐(tri‐fluoromethylsulfonyl)imide (LiTFSI) dimethyl sulfoxide (DMSO) electrolyte has been detected “in‐operando” by fluorescence quenching of 9,10‐dimethylanthracene, DMA. Furthermore, the formation of 1O2 during ORR requires Li+ ions, while in the presence of the efficient physical 1O2 quencher, sodium azide, DMA fluorescence quenching is negligible. Addition of Li+ ions to superoxide solution in DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 29 publications
(31 reference statements)
2
48
0
Order By: Relevance
“…For example, the absorption/emission spectra of DMA appear 300–700 nm region, and their signals are reduced after capturing 1 O 2 via [4+2] cycloaddition (Figure 4c) [5b] . Various examples of adapting trapping agents to Li−O 2 and Na–O 2 cells are summarized in Table S1 [5,13a,14,21,22,24,26,31] in the Supporting Information. Delithiated lithium iron phosphate (Li 1− x FePO 4 ) was used as the anode to avoid unintended decomposition of the trapping agents.…”
Section: Detection Of 1o2 In Li−o2 Cellsmentioning
confidence: 99%
“…For example, the absorption/emission spectra of DMA appear 300–700 nm region, and their signals are reduced after capturing 1 O 2 via [4+2] cycloaddition (Figure 4c) [5b] . Various examples of adapting trapping agents to Li−O 2 and Na–O 2 cells are summarized in Table S1 [5,13a,14,21,22,24,26,31] in the Supporting Information. Delithiated lithium iron phosphate (Li 1− x FePO 4 ) was used as the anode to avoid unintended decomposition of the trapping agents.…”
Section: Detection Of 1o2 In Li−o2 Cellsmentioning
confidence: 99%
“…S3) [27]. The method is now the widely adopted standard method to detect 1 O2 in nonaqueous electrochemical environments [17,27,28,34,[36][37][38].…”
Section: Resultsmentioning
confidence: 99%
“…Azide could be an interesting quencher for these energy storage systems, as recently demonstrated for both Li and Na-O 2 batteries (Córdoba et al, 2019;Lozano et al, 2020). However, due to the explosive potential and safety concerns, azide should be avoided whenever possible if there is a reasonable alternative.…”
Section: How Singlet Oxygen Can Be Deactivated?mentioning
confidence: 99%
“…Wandt et al demonstrated that this degradation was ascribed to the presence of intermediate species such as the generation of singlet oxygen at charge potentials between 3.55 and 3.75 V (vs. Li + /Li) (Wandt et al, 2016 ). The latest studies on the mechanisms involving the generation of singlet oxygen in Li-O 2 batteries, conclude that the major source of 1 O 2 is the disproportionation (also known as dismutation) of LiO 2 ( Figure 2 , reaction 8) through the following mechanism (Córdoba et al, 2019 ; Mourad et al, 2019 ; Wang and Lu, 2020 ):…”
Section: What Are the Implications For Metal-o 2 Bmentioning
confidence: 99%